STUDI ISLAM DALAM PENDEKATAN SOSIOLOGI - Nori Nori; Sulastri Sulastri; Ubabuddin Ubabuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Background: In simple terms, sociology can be interpreted as a science that describes the state of society complete with structure, layers, and various other social symptoms that are interconnected. With this science a phenomenon can be analyzed by presenting the factors that drive the occurrence of the relationship, social mobility and the beliefs that underlie the occurrence of the process.